Partially dielectric loaded planar Vivaldi array antenna for forward-looking GPR applications - Caliskan, Alper; Hosgor, Yasin; Turk, Ahmet Serdar; Kizilay, Ahmet (WILEY, 2024)
This paper presents a novel two-element partially dielectric loaded planar Vivaldi antenna array for ultra-wideband applications. This array is capable of operating between 380 MHz and 3 GHz and is designed on a 1.6-mm thick low-cost FR4 substrate with total size of 25 x 330 x 430 mm(3). Innovative approaches to various gain enhancement techniques such as partial dielectric loading, corrugations, and U-shaped back reflector used for planar Vivaldi antennas, are collectively employed in this design. Various elements of the array are interconnected. The two-element Vivaldi array is fed by using a power divider. The array is designed by using a full-wave three-dimensional EM simulation tool. The designed antenna is manufactured and then measured. The simulation and measurement results are found to be consistent with each other.
Keywords: array antenna; partial dielectric load; planar Vivaldi antenna; ultra-wide band; HIGH-GAIN; DESIGN; Engineering; Optics